Feasibility Study of Intelligent Three-Dimensional Accurate Liver Reconstruction Technology Based on MRI Data - Cao, Shaodong; Li, Huan; Dong, Suyu; Gao, Zhenxuan (Frontiers in Medicine, 2022)
Intelligent three-dimensional reconstruction technology plays an important role in the diagnosis and treatment of diseases, and has been widely used in liver assisted surgery. At present, the three-dimensional reconstruction information of liver is mainly obtained based on CT enhancement data, and has been commercialized. However, there are few reports on the display of three-dimensional reconstruction information of liver based on magnetic resonance imaging.The purpose of this study is to propose a new idea of intelligent three-dimensional liver reconstruction based on magnetic resonance imaging technology, and verify its feasibility. Two different liver scanning data (CT and MRI) were selected from the same batch of patients at the same time (Patients with a time interval of no more than two weeks and without surgery). The results of liver volume, segmentation, tumor and simulated surgery based on MRI volume data were compared with those based on CT data.The results show that the results of three-dimensional reconstruction based on MRI data are highly consistent with those based on CT three-dimensional reconstruction. At the same time, in addition to providing the information provided by CT three-dimensional reconstruction, it also has its irreplaceable advantages. For example, multi-phase (early, middle and late arterial, hepatobiliary, etc.) scanning of MRI technology can provide more disease information and display of biliary diseases. In a word, magnetic resonance imaging technology can be used for three-dimensional reconstruction of the liver, and a new feasible and effective method to show the liver itself and its disease characteristics is proposed.